Development of electromobility in Poland: analysis of the social perception and acceptance of electric cars by Poles - Karaś, Zuzanna (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents’ Perspective, 2024)
The chapter focuses on the development of electromobility in Poland. It describes the essence of electromobility, conditions of its development, environmental aspects of electric vehicles and limitations of the environmental effect of electromobility. In addition, the demand for this type of cars in Poland was analysed. The main aim of the study, the results of which are presented in this chapter, was to assess the perception of electromobility among Poles and to identify the intention to purchase an electric car. A quantitative research method was used – the survey technique, which was carried out on a sample of 141 people. The results of the survey indicate that respondents mostly (66%) perceive electric cars as environmentally friendly, but they are aware of their limitations in achieving the environmental effect. The majority of respondents are users of internal combustion vehicles, who are most likely to have a negative view of electric cars in terms of purchase and operating costs, insufficient range accompanied by an underdeveloped vehicle charging infrastructure. Electric car owners, on the other hand, emphasise the financial benefits in the form of low running costs, the possibility of free parking in paid parking zones and the environmental benefits (low noise and CO2 emissions). More than 37% of those surveyed expressed a desire to purchase an electric car in the future.